1999
DOI: 10.2307/3761255
|View full text |Cite
|
Sign up to set email alerts
|

Acaulospora colossica sp. nov. from an Old Field in North Carolina and Morphological Comparisons with Similar Species, A. laevis and A. koskei

Abstract: Abstract:A new arbuscular mycorrhizal fungal species, Acaulospora colossica, ( Glomales, Acaulosporaceae) is described, and its distribution and seasonality discussed. Spores of A. colossica develop from saccules that empty their contents in the developing spores. Spore wall structure consists of 3 layers, all originating from the subtending hyphae. The two inner layers are laminated. The outermost spore wall layer is typically sloughed off before the spores mature. Two inner walls arise sequentially. Both inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
2
9
0
1
Order By: Relevance
“…We have also found evidence that AM fungi differ in their seasonality, with some fungi sporulating in late spring and others sporulating at the end of summer ( Figure 5; Schultz et al 1999). As the spores represent the dormant state of the fungus, the physiologically active state is most likely the mirror image of the seasonal spore counts.…”
Section: Seasonalitymentioning
confidence: 56%
See 2 more Smart Citations
“…We have also found evidence that AM fungi differ in their seasonality, with some fungi sporulating in late spring and others sporulating at the end of summer ( Figure 5; Schultz et al 1999). As the spores represent the dormant state of the fungus, the physiologically active state is most likely the mirror image of the seasonal spore counts.…”
Section: Seasonalitymentioning
confidence: 56%
“…These differences in sporulation patterns within this field, therefore, quite likely reflect distinct differences in seasonal activity of these fungal species. In fact, further work on these fungi confirms the distinct seasonal behavior of these species (Schultz et al 1999), with Ac. colossica being physiologically active during the cool season and dormant during the summer months, while Gi.…”
Section: Implications Of Am Fungal Diversity For Plant Ecologymentioning
confidence: 69%
See 1 more Smart Citation
“…Hostspecificity in fungal population growth rates may contribute to the maintenance of fungal diversity (Bever et al, 1996); in addition, the high diversity of AM fungi might result from a temporal partitioning of the habitat. In fact, prior sampling suggests that fungi differ in their seasonalities: Schultz, Bever, and Morton (1999) observed that Acaulospora colossica sporulates in spring, but other species, particularly Gigaspora gigantea, are observed to sporulate in winter (Schultz, 1996). In this study, we aimed to rigorously test for the distinct seasonalities of Ac.…”
mentioning
confidence: 99%
“…Esporos de A. koskei podem ser confundidos com os de A. colossica Schultz, Bever & Morton principalmente pela coloração que se superpõe (Schultz et al 1999 Distribuição e habitat: conhecido para dunas na Polônia (Blaszkowski 1995), áreas alagadiças dos EUA (Miller & Bever 1999) Rothwell & Trappe, Mycotaxon 8: 472. 1979.…”
Section: Resultsunclassified